1986
DOI: 10.3164/jcbn.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amino Acid Pattern of Type II Citrullinemic Patients and Effect of Oral Administration of Citrulline

Abstract: SummaryTwenty-four cases of type II citrullinemia, diagnosed as such based on enzymatic analysis showing a decreased enzyme content of kinetically-normal argininosuccinate synthetase in the liver, showed the following features of their serum amino acid patterns : 1) Serum arginine levels were higher than in controls and were significantly correlated with serum citrulline levels. 2) Serum alanine, serine, glycine, and branchedchain amino acids (valine + isoleucine + leucine) were significantly lower than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…Blood citrulline concentrations failed to rise to more than ϩ2 SD in only one of the 20 individuals with SLC25A13 mutations. A previous study reported high threonine/serine ratio and low branched chain amino acid levels in CTLN2 (2). Also in this study, serine and leucine plus isoleucine in patients with SLC25A13 were similar or slightly decreased to those in controls, as shown in Figure 1.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Blood citrulline concentrations failed to rise to more than ϩ2 SD in only one of the 20 individuals with SLC25A13 mutations. A previous study reported high threonine/serine ratio and low branched chain amino acid levels in CTLN2 (2). Also in this study, serine and leucine plus isoleucine in patients with SLC25A13 were similar or slightly decreased to those in controls, as shown in Figure 1.…”
supporting
confidence: 60%
“…Abbreviations CTLN2, adult-onset type II citrullinemia NICCD, neonatal intrahepatic cholestasis caused by citrin deficiency NMS, newborn mass screening CTLN2 (OMIM #603471) is characterized by late onset (age, 11-79 y), frequent attacks of hyperammonemia, mental derangement, sudden attacks of unconsciousness, and ultimately death within a few years of onset (1,2). CTLN2 is caused by mutations of the SLC25A13 gene (3)(4)(5), which is localized on chromosome 7q21.3 and encodes a calcium-ratio in the cytosol and failure of aspartate supply from the mitochondria to the cytoplasm for synthesis of argininosuccinate, resulting in high blood levels of citrulline and ammonia.…”
Section: (Pediatr Res 56: 608-614 2004)mentioning
confidence: 99%
“…9,11,12 In patients with CTLN2, serum arginine concentrations are increased as well as citrulline concentrations. 21 Furthermore, argininosuccinic acid is excreted in the urine. 22 Establishment of the DNA diagnosis for citrin de¢ciency in CTLN2 revealed that SLC25A13 mutations are also the molecular cause of a particular type of neonatal hepatitis: neonatal intrahepatic cholestasis caused by citrin de¢ciency: NICCD, OMIM #605814.…”
Section: ^20mentioning
confidence: 99%
“…The liver-specific ASS deficiency in CTLN2 patients leads to a lesser increase in plasma Cit levels than that in CTLN1 patients, proportionally elevated levels of plasma arginine (Arg), and an increase in urine argininosuccinate (36)(37)(38). Furthermore, CTLN2 patients exhibit an increase in their plasma threonine-to-serine (Thr/Ser) ratio (13,37) as well as elevated levels of pancreatic secretory trypsin inhibitor (PSTI) in serum, the latter resulting from its up-regulated transcriptional expression in the liver (13,16).…”
mentioning
confidence: 99%